Corneal nerve loss in children with type 1 diabetes mellitus without retinopathy or microalbuminuria - Gad, Hoda (J Diabetes Investig, 2020)
AIMS/INTRODUCTION: Corneal confocal microscopy is a rapid, non‐invasive ophthalmic technique to identify subclinical neuropathy. The aim of this study was to quantify corneal nerve morphology in children with type 1 diabetes mellitus compared with age‐matched healthy controls using corneal confocal microscopy. MATERIALS AND METHODS: A total of 20 participants with type 1 diabetes mellitus (age 14 ± 2 years, diabetes duration 4.08 ± 2.91 years, glycated hemoglobin 9.3 ± 2.1%) without retinopathy or microalbuminuria and 20 healthy controls were recruited from outpatient clinics. Corneal confocal microscopy was undertaken, and corneal nerve fiber density (n/mm(2)), corneal nerve branch density (n/mm(2)), corneal nerve fiber length (mm/mm(2)), corneal nerve fiber tortuosity and inferior whorl length (mm/mm(2)) were quantified manually. RESULTS: Corneal nerve fiber density (22.73 ± 8.84 vs 32.92 ± 8.59; P < 0.001), corneal nerve branch density (26.19 ± 14.64 vs 47.34 ± 20.01; P < 0.001), corneal nerve fiber length (13.26 ± 4.06 vs 19.52 ± 4.54; P < 0.001) and inferior whorl length (15.50 ± 5.48 vs 23.42 ± 3.94; P < 0.0001) were significantly lower, whereas corneal nerve fiber tortuosity (14.88 ± 5.28 vs 13.52 ± 3.01; P = 0.323) did not differ between children with type 1 diabetes mellitus and controls. Glycated hemoglobin correlated with corneal nerve fiber tortuosity (P < 0.006) and aspartate aminotransferase correlated with corneal nerve fiber density (P = 0.039), corneal nerve branch density (P = 0.003) and corneal nerve fiber length (P = 0.037). CONCLUSION: Corneal confocal microscopy identifies significant subclinical corneal nerve loss, especially in the inferior whorl of children with type 1 diabetes mellitus without retinopathy or microalbuminuria.